THE STABILITY OF CEPHEID PULSATIONS - Turner, D. G.; Berdnikov, L. N. (Одеські астрономічні публікації, 2017)
Analyses of Cepheid period changes using O-C diagrams are used to establish the direction of evolution of individual stars through the instability strip. The superposition of random in period on O-C data is less easy to interpret. Such chaotic behavior is a standard feature of Mira and RV Tauri variables according to the work of Percy, but has not been examined in detail for Cepheids. Unlike the situation for cooler classes of pulsators, most Cepheids do not exhibit random in period. Binarity plays only a minor role in the scatter in O-C data.